High quality genome assembly of the brown hare (Lepus europaeus) with chromosome-level scaffolding - Michell, Craig; Collins, Joanna; Laine, Pia K.; Fekete, Zsófia; Tapanainen, Riikka; Wood, Jonathan M. D.; Goffart, Steffi; Pohjoismäki, Jaakko L. O. (Peer Community Journal)

(untitled)
We present here a high-quality genome assembly of the brown hare (Lepus europaeus Pallas), based on a fibroblast cell line of a male specimen from Liperi, Eastern Finland. This brown hare genome represents the first Finnish contribution to the European Reference Genome Atlas pilot effort to generate reference genomes for European biodiversity. The genome was assembled using 25X PacBio HiFi sequencing data and scaffolded utilizing a Hi-C chromosome structure capture approach. After manual curation, the assembled genome length was 2,930,972,003 bp with N50 scaffold of 125.8 Mb. 93.16% of the assembly could be assigned to 25 identified chromosomes (23 autosomes plus X and Y), matching the published karyotype. The chromosomes were numbered according to size. The genome has a high degree of completeness based on the BUSCO score (mammalia_odb10 database), Complete: 96.1% [Single copy: 93.1%, Duplicated: 3.0%], Fragmented 0.8%, and Missing 2.9%. The mitochondrial genome of the cell line was sequenced and assembled separately. The final annotated genome has 30,833 genes of which 21,467 code for a polypeptide. The brown hare genome is particularly interesting as this species readily hybridizes with the mountain hare (Lepus timidus L.) at the species contact zone in northern Eurasia, producing fertile offspring and resulting in gene flow between the two species. In addition to providing a useful comparison for population studies, the genome can offer insight into the chromosomal evolution among Glires in general and Lagomorpha in particular. The chromosomal assembly of the genome also demonstrates that the cell line has not acquired karyotypic changes during culture.